Pemanfaatan Kompos Eceng Gondok untuk Pertumbuhan dan Hasil Tanaman Pakcoy di Tanah Gambut - Wahdah, Rabiatul; Nugraha, Muhammad Imam; Safitri, Noorlena (Jurnal Agroekoteknologi, 2024)
This study examines organic matter in the form of swamp plant-derived compost, namely water hyacinth.  The study's objective was to ascertain how water hyacinth compost affected on peat soil which is known to have low soil fertility and is a problem in pakcoy cultivation. This study was a polybag scale experimental study using a one-factor Completely Randomized Design (CRD), namely water hyacinth compost with 5 levels of treatment with 4 replications so that there were 20 experimental units, the treatment consisted of p0 = 0 g polybag-1 (without treatment), p1 = 45 g polybag-1 water hyacinth compost p2 = 89 g polybag-1 water hyacinth compost, p3 = 134 g polybag-11 water hyacinth compost, p4 = 178 g polybag-1water hyacinth compost. The research was started by making compost from water hyacinth added with chicken and cow manure to enrich the compost content. Once the compost has matured it is applied to the peat soil and incubated for a week. Pakcoy seedlings are planted when the plants have 2-4 leaves, then maintenance, observation of plant growth and yield, then harvesting will be carried out. In addition, an analysis of compost and soil samples after incubation was also carried out.  This indicates that the application of water hyacinth compost affected the growth of pakcoy plants and changed the chemical characteristics of peat soils.  134 g polybag-1 of water hyacinth compost has the greatest effect on the growth and yield of pakcoy plants, while the chemical characteristics of peat soils have varied effects and there has been an increase.KeywordsPeat Soil; Compost; Water Hyacinth; Pakcoy